Avaliação da modulação autonômica cardiovascular de repouso e limitação ventilatória ao exercício físico em indivíduos com diabetes mellitus tipo 2 - Tonello, Sílvia Cristina Garcia de Moura (Universidade Federal de São Carlos, 2016)
This thesis consisted of two studies described below. Study I aimed to evaluate whether heart period (HP) and systolic arterial pressure (SAP) variability indexes are sensitive enough to detect the autonomic dysfunction in patients with type 2 diabetes (DM) without cardiovascular autonomic neuropathy (CAN) and other neuropathies. We evaluated 34 men with DM without neuropathy manifests (GDM) and 34 apparently healthy individuals (GC), with mean of age equal 54±6,05 e 54,50±5,96, respectively. The protocol consisted of 15 minutes of recording the variability of HP and SAP at rest in the supine position (REST) and after active standing (STAND). HRV and APV were analyzed by spectral method and the indexes that estimate the baroreflex sensitivity (BRS) through the spectral and sequence method. The high frequency band (HF, 0.15 to 0.5 Hz) of the HP was lower in the REST in GDM than in the control group, while in the STAND there was no difference between groups. The band of low frequency (LF, 0.04 to 0.15 Hz) in systolic arterial pressure (SAP) was similar in REST and increased during STAND in both groups. BRS estimated in the HF band and indexes of baroreflex sequence method was lower in GDM than in GC in supine position and they decreased during STAND in both groups. Thus, we concluded that the vascular sympathetic control and baroreflex response after active postural change are preserved in the population studied, but the vagal control of heart rate and cardiac baroreflex presented reduced in GDM, showing that the indexes of cardiovascular variability are sensitive enough to typify the early, peculiar, signs of autonomic dysfunction in type-2 DM patients well before CAN becomes manifest. Following evaluating also individuals with type 2 diabetes mellitus (DM) without neuropathy manifests, the Study II aimed to evaluating the EFL using the expiratory flow-volume loop (EFVL) during two intensities of exercise, and additionally assess if it is related to the reduction of aerobic capacity in DM. Forty men were evaluated and equally divided in two groups matched for age, i.e. subjects with DM (GDM) and control group (GC). Initially, the volunteers performed cardiopulmonary exercise testing (CPET). After this, they underwent two constant load tests (CWETs) at moderate and high intensity exercise in order to evaluate and classify the EFL by EFVL method, which consisted of plotting the EFVL within the xvii maximal volume flow loop (MAFV). Statistical tests were applied and p< 0.05 was considered as significant. The GDM presented decreased of aerobic capacity when compared to GC, however GDM showed similar responses to GC for the LFE in moderate intensity, despite a greater number of individuals with severe LFE in high intensity of exercise. In addition, it was not found the relationship between the LFE and aerobic capacity of GDM, that is, the low aerobic capacity of GDM is not related LFE. Thus, the studies presented in this thesis brought important contributions to the improvement in the treatment of individuals with DM due to findings related to vagal commitment and possible pulmonary subclinical impairment and circulatory adjustments during the exercise, providing assistance in exercise prescription in the cardiopulmonary rehabilitation for this population.
Assessment of cardiovascular autonomic modulation at rest and ventilatory limitation to exercise in patients with type 2 diabetes mellitus
Keywords: Controle cardiovascular; Sistema nervoso autonômico; Barorreflexo; Função ventilatória; Teste cardiopulmonar; Cardiovascular control; Autonomic nervous system; Barorreflex; Ventilatory function; Cardiopulmonary exercise testing; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL